Quantitative laser-induced breakdown spectroscopy mapping of centerline segregation via optical emissions of Mn and Cr in steel wire rod products. (December 2022) - Jung, Sehoon; Kim, Sunhye; Kim, Sungnam; Park, Ikbum; Moon, Youngmin; Heo, Jeong-Heon; Nam, Sang-Ho; Lee, Yonghoon
Abstract: A steel wire rod is one of the cast steel products used for springs to absorb repeated shocks, particularly in harsh conditions. Quality assessment of steel wire rods is critically important to prevent unwanted breakage during their lifetime. However, centerline segregation is the most common cause of weakened steel wire rods. Currently, centerline segregation is monitored using an optical microscope and an electron probe microanalyzer (EPMA). Herein, we demonstrate quantitative concentration mapping of Mn and Cr, the representative alloying elements, in steel wire rods using laser-induced breakdown spectroscopy (LIBS) as an alternative centerline segregation monitoring methodology. Sensitivity, detection limit, precision, and spatial resolution were found to be enough to observe centerline segregation. Concentration maps obtained by LIBS were very similar to those from EPMA. Microscopic matrix changes due to segregation were also identified. The resulting decrease in plasma temperatures was rationalized by formation of metal carbides that hardened local segregated areas. Considering the rapid multi-elemental mapping capability of LIBS in open air, LIBS is suggested as a practical alternative to optical microscope limited to carbon mapping and EPMA that needs high-vacuum equipment for screening faulty steel wire rod products. Graphical Abstract: The centerline segregation of Mn and Cr in steel wire rods are rapidly monitored by laser-induced breakdown spectroscopy mapping. ga1 Highlights: A LIBS instrument for rapid elemental mapping for steel wire rods was developed. Centerline segregation of Mn and Cr was well observed by the LIBS instrument. Microscopic matrix changes due to the centerline segregation were identified and rationalized. LIBS outperforms optical microscopy in sample preparation and multiple element mapping. LIBS is faster and more cost-effective than EPMA.